Genotype–phenotype correlation in contactin-associated protein-like 2 (CNTNAP-2) developmental disorder - Gianluca D’Onofrio; Andrea Accogli; Mariasavina Severino; Haluk Caliskan; Tomislav Kokotović; Antonela Blazekovic; Kristina Gotovac Jercic; Silvana Markovic; Tamara Zigman; Krnjak Goran; Nina Barišić; Vlasta Duranovic; et al. (Human Genetics, 2023)
Contactin-associated protein-like 2 ( CNTNAP2 ) gene encodes for CASPR2, a presynaptic type 1 transmembrane protein, involved in cell–cell adhesion and synaptic interactions. Biallelic CNTNAP2 loss has been associated with “Pitt-Hopkins-like syndrome-1” (MIM#610042), while the pathogenic role of heterozygous variants remains controversial. We report 22 novel patients harboring mono- ( n = 2) and bi-allelic ( n = 20) CNTNAP2 variants and carried out a literature review to characterize the genotype–phenotype correlation. Patients (M:F 14:8) were aged between 3 and 19 years and affected by global developmental delay (GDD) ( n = 21), moderate to profound intellectual disability ( n = 17) and epilepsy ( n = 21). Seizures mainly started in the first two years of life (median 22.5 months). Antiseizure medications were successful in controlling the seizures in about two-thirds of the patients. Autism spectrum disorder (ASD) and/or other neuropsychiatric comorbidities were present in nine patients (40.9%). Nonspecific midline brain anomalies were noted in most patients while focal signal abnormalities in the temporal lobes were noted in three subjects. Genotype–phenotype correlation was performed by also including 50 previously published patients (15 mono- and 35 bi-allelic variants). Overall, GDD ( p < 0.0001), epilepsy ( p < 0.0001), hyporeflexia ( p = 0.012), ASD ( p = 0.009), language impairment ( p = 0.020) and severe cognitive impairment ( p = 0.031) were significantly associated with the presence of biallelic versus monoallelic variants. We have defined the main features associated with biallelic CNTNAP2 variants, as severe cognitive impairment, epilepsy and behavioral abnormalities. We propose CASPR2-deficiency neurodevelopmental disorder as an exclusively recessive disease while the contribution of heterozygous variants is less likely to follow an autosomal dominant inheritance pattern.